(3OjhGf YeQ Hf CHj QHjYIs - (3GHf CHj QHjYI , YeQ Hf YHO Gddg Hf CHj QHjYI GdeNRhej, CHh GdNWGH,J (B93 (3g` s
(3ChdgG (B:s
(3RYe GdgjKe Hf YOj bGd CNHQfG CHhGdZSjd Yf YcQeI bGd(B: (3cfG YfO GHf YHGS aLGAg abGd dg GHf YHGS(B: (3jGHf CNj GfTOfj aCfTO bhdg(B: (3Cef Bd fYe CfJ ZGO aeHcQ s
(3BNQgG (B:s
(3adh cfJ HGdOGQ GdJj egHW GdUaG eQVJ EPG eG ZGH Yfj eYdd s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B211s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B165 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B803s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCgdjI HHGQjS (B(9533) s
Keywords: (3GdCOHs